Systematic review of low-income and middle-income country perceptions of visiting surgical teams from high-income countries. Issue 4 (28th April 2022) - Velin, Lotta; Lantz, Adam; Ameh, Emmanuel A.; Roy, Nobhojit; Jumbam, Desmond T.; Williams, Omolara; Elobu, Alex; Seyi-Olajide, Justina; Hagander, Lars
Abstract : Background: The shortage of surgeons, anaesthesiologists and obstetricians in low-income and middle-income countries (LMICs) is occasionally bridged by foreign surgical teams from high-income countries on short-term visits. To advise on ethical guidelines for such activities, the aim of this study was to present LMIC stakeholders' perceptions of visiting surgical teams from high-income countries. Method: We performed a systematic review according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines in November 2021, using standardised search terms in PubMed/Medline (National Library of Medicine), EMBASE (Elsevier), Global Health Database (EBSCO) and Global Index Medicus, and complementary hand searches in African Journals Online and Google Scholar. Included studies were analysed thematically using a meta-ethnographic approach. Results: Out of 3867 identified studies, 30 articles from 15 countries were included for analysis. Advantages of visiting surgical teams included alleviating clinical care needs, skills improvement, system-level strengthening, academic and career benefits and broader collaboration opportunities. Disadvantages of visiting surgical teams involved poor quality of care and lack of follow-up, insufficient knowledge transfers, dilemmas of ethics and equity, competition, administrative and financial issues and language barriers. Conclusion: Surgical short-term visits from high-income countries are insufficiently described from the perspective of stakeholders in LMICs, yet such perspectives are essential for quality of care, ethics and equity, skills and knowledge transfer and sustainable health system strengthening. More in-depth studies, particularly of LMIC perceptions, are required to inform further development of ethical guidelines for global surgery and support ethical and sustainable strengthening of LMIC surgical systems.